Fluoride Removal and Recovery from Groundwater Using an Integrated Reverse Osmosis–Membrane Crystallization Process - Wuhib Zeine Ousman; Esayas Alemayehu; Patricia Luis (Clean Technologies, 2025)
Elevated fluoride levels in drinking water pose a significant health risk for communities relying on groundwater in the Ethiopian Central Rift Valley. This study aims at characterizing real groundwater samples from the Ethiopian Central Rift Valley and evaluating the performance of an integrated membrane process based on reverse osmosis (RO) and membrane crystallization (MCr) for fluoride removal and its recovery as mixed fluoride salts. Groundwater analysis revealed fluoride concentrations of 20.8 mgL−1 at the Meki-01 site and 22.7 mgL−1 at the Meki-02 site, both exceeding the WHO guideline of 1.5 mgL−1. In addition, total dissolved solids exceeded 1000 mgL−1 at both sites, classifying the water as brackish. A commercial RO membrane demonstrated excellent fluoride and ion rejection, with fluoride removal rates exceeding 99%. The total dissolved solids (TDS) removal efficiency reached 89%. The mean water permeability of the membrane was 4.52 Lm−2h−1bar−1. The retentate produced in the RO unit reached a concentration of 70 mgL−1, which was then treated using osmotic membrane distillation–crystallization (OMD-Cr) and/or vacuum membrane crystallization (VM-Cr). This process facilitated the recovery of mixed salts while achieving an almost zero-liquid discharge. The study confirms the successful removal of fluoride and its recovery as mixed salt, along with the recovery of water in an environmentally friendly and manageable way.